UPAYA MENINGKATKAN KREATIVITAS DALAM MEMECAHKAN MASALAH DENGAN MENGGUNAKAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) - Windi A Wansaubun (Arfak Chem: Chemistry Education Journal, 2020)
Abstact The ability to think creatively is one of the skills that every student must have. The ability to think creatively can be improved by using the Problem Based Solving (PBS) learning model. By giving a problem and applying the CPS model in learning it can directly affect students. This study aims to see the effect of the Problem Based Solving learning model on the creativity of students in solving problems. The learning method uses an experimental group and a control group with cluster random sampling technique. In this study, it can be said to be successful when the students solve increasing problems. The learning process can be built by several factors, namely the media, curriculum, models, methods, and learning approaches used. Based on the literature that has been studied using the Problem Based Solving learning model, it has an effect on problem management problems. Keywords: Critical Thinking Skills, Student, Creative Problem Solving (CPS)